2017
DOI: 10.3168/jds.2016-11559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary roughage level on chewing activity, ruminal pH, and saliva secretion in lactating Holstein cows

Abstract: Increasing dietary roughage level is a commonly used strategy to prevent subacute ruminal acidosis. We hypothesized that high-roughage diets could promote chewing activity, saliva secretion, and hence more alkaline to buffer rumen pH. To verify the hypothesis, 12 multiparous Holstein cows in mid lactation were randomly allocated to 4 treatments in a triplicated 4 × 4 Latin square experiment with one cow in each treatment surgically fitted with a ruminal cannula. Treatments were diets containing 40, 50, 60, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 37 publications
(61 reference statements)
9
45
0
1
Order By: Relevance
“…Similar effects of forage particle size on eating and ruminating time were reported by others (Yang et al, 2001b;Kowsar et al, 2008;Akbari-Afjani et al, 2014;Alamouti et al, 2014). However, increased eating time does not always eliminate the need for longer rumination time per kilogram of DM when intake of long forage particles is increased through increased F:C ratio (Jiang et al, 2017) or particle size (Zhang et al, 2010;Kammes and Allen, 2012). For example, Jiang et al (2017) fed dairy cows 4 diets that ranged from 40 to 70% forage.…”
Section: Chemical and Physical Characteristics Of The Dietsupporting
confidence: 57%
See 1 more Smart Citation
“…Similar effects of forage particle size on eating and ruminating time were reported by others (Yang et al, 2001b;Kowsar et al, 2008;Akbari-Afjani et al, 2014;Alamouti et al, 2014). However, increased eating time does not always eliminate the need for longer rumination time per kilogram of DM when intake of long forage particles is increased through increased F:C ratio (Jiang et al, 2017) or particle size (Zhang et al, 2010;Kammes and Allen, 2012). For example, Jiang et al (2017) fed dairy cows 4 diets that ranged from 40 to 70% forage.…”
Section: Chemical and Physical Characteristics Of The Dietsupporting
confidence: 57%
“…However, increased eating time does not always eliminate the need for longer rumination time per kilogram of DM when intake of long forage particles is increased through increased F:C ratio (Jiang et al, 2017) or particle size (Zhang et al, 2010;Kammes and Allen, 2012). For example, Jiang et al (2017) fed dairy cows 4 diets that ranged from 40 to 70% forage. Eating time increased (min/d, min/kg of DM, min/kg of NDF) with increasing F:C ratio of the diet.…”
Section: Chemical and Physical Characteristics Of The Dietmentioning
confidence: 99%
“…Consistent with the unchanged ruminating periods and time length per period, daily ruminating time was not affected by treatment. The constant eating and periods of rumination were consistent with previous studies (Jiang et al., ; Kononoff & Heinrichs, ; Krause & Combs, ), except for the study by Krause, Combs, and Beauchemin (), which reported that daily meals and periods decreased when FPS was reduced. These differences might be attributable to a lower forage level (39.3%) and NDF content (24%), resulting in SARA.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies (Jiang et al, 2017;Yang & Beauchemin, 2009), daily variations in ruminal pH for all diets peaked just before the 05:30 and 17:30 hr feedings (Figure 1), which may be attributable to limited feed intake and less eating activity during several hours preceding the measurements. Consistent with the higher DM effective degradability of oaten hay than that of wild-rye hay (49.5 vs. 34.0%), the DMI increased from 21.1 to 22.2 kg/day when FPS was reduced.…”
Section: )supporting
confidence: 90%
See 1 more Smart Citation